Penerapan Media Jam Pintar Untuk Meningkatkan Kemampuan Membaca Suku Kata Pada Kelompok B Di TK Terpadu Alkhairiyah Surabaya Tahun Pelajaran 2022/2023 - Widiyanti, Sulis; Virdaus, Varia virdania (Universitas Narotama, 2024)
This research was motivated by students' ability to read syllables is still low, 36% of students still have difficulty in distinguishing letters. The purpose of this study is to improve the ability to read syllables with the application of smart watch media. This type of research is a classroom action research using the research subjects of group B students of Alkhairiyah Integrated Kindergarten for the 2022/2023 academic year as many as 21 students consisting of 12 boys and 9 girls, data obtained through preobservation. Data collection techniques through observation, tests and documentation. The study was conducted in 2 cycles, each cycle consisted of 2 meetings. The results of the study obtained the average completeness of the ability to read syllables with smart watch media in the precycle 36%, cycle 1 children's ability increased 47% and after action was carried out in cycle 2 even more increased the average completeness of 81%.